The Impact of Pet Ownership on Healthcare-Seeking Behavior in Individuals Experiencing Homelessness. (3rd September 2022) - Ramirez, Vickie; Frisbie, Lauren; Robinson, Jovien; Rabinowitz, Peter M.
ABSTRACT: The objective of this research was to understand the effect of pet ownership on healthcare-seeking behavior among persons experiencing homelessness with animals. Mixed-method, semi-structured interviews were conducted with 44 people experiencing homelessness with animals in Seattle, Washington to collect stories of barriers and facilitators due to animal ownership, health-seeking behaviors for themselves and their animals, and self-assessed health status and health conditions of the owners and their pets. The interviews also explored the ways in which the participants would like to receive healthcare services for themselves and their animals. Quantitative results showed that the medical care sourced for pets exceeded that for the owner's own health, with 86% of participants seeking healthcare for themselves within the past year and 93% of participants seeking veterinary care for their pet within the past year. Results also displayed self-described health of the animal faring better than that of the owner, with 47% of participants reported being "Healthy" or "Very healthy" compared with 90% of pets being reported as the same. Themes emerging from the qualitative research included that persons experiencing homelessness with animals place a high value on the health and welfare of their pets, that the animals can pose a barrier to traditional health services and access to overall services, and that the owner's need for animal companionship and support is high. These findings suggest that utilizing the human–animal bond and creating integrated (human and animal), interprofessional health services using a One Health approach for unhoused populations owning pets can reduce barriers to services and improve both human and animal health. In an integrated health clinic setting, the owner may seek care for their animal but stay for the human healthcare.